2020
DOI: 10.1155/2020/8819771
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of miR-204 on Doxorubicin-Induced Cardiomyocyte Injury via HMGB1

Abstract: The toxicity of doxorubicin (DOX) limits its clinical application. Nevertheless, at present, there is no effective drug to prevent DOX-induced cardiac injury. miR-204 is a newly discovered miRNA with many protective effects on cardiovascular diseases. However, little research has been done on the effects of miR-204 on DOX-induced cardiac injury. Our study is aimed at investigating the effect of miR-204 on DOX-induced myocardial injury. An adenoassociated virus system was used to achieve cardiac-specific overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…30) In addition, Du, et al demonstrated that HMGB1 could attenuate the miR-204-medated prevention on DOX-induced cardiotoxic effects. 31) In our study, we discovered that DOX treatment increases the HMGB1 expression level. Furthermore, HMGB1 abolished the protective role of miR-409-3 p on cardiomyocytes under DOX treatment.…”
Section: Discussionmentioning
confidence: 63%
“…30) In addition, Du, et al demonstrated that HMGB1 could attenuate the miR-204-medated prevention on DOX-induced cardiotoxic effects. 31) In our study, we discovered that DOX treatment increases the HMGB1 expression level. Furthermore, HMGB1 abolished the protective role of miR-409-3 p on cardiomyocytes under DOX treatment.…”
Section: Discussionmentioning
confidence: 63%
“…Zhang et al found that rosuvastatin reduced the secretion of TNF-α and IFN-γ by reducing HMGB1 levels [211]. Du et al found that miR-204 levels were decreased after DOX treatment, and miR-204 overexpression targeted HMGB1 to directly reduce its levels, thus exerting a cardioprotective effect [212]. Besides, myeloid differentiation protein 1(MD-1) appears to be related to the regulation of TLR4 expression and DOXinduced myocardial inflammation.…”
Section: Hmgb1/tlr4/mapks/nf-κb Signaling Pathwaymentioning
confidence: 99%
“…miRNA can play a significant role in the onset and progression of cardiovascular disease by coordinating various disease pathways. MiR-204 is a newly discovered miRNA with multiple protective effects on cardiovascular diseases [ 8 ]. It has been found that miR-204 can protect myocardial cells from ischemia/reperfusion injury by regulating apoptosis, and the serum miR-204 expression considerably reduced in patients with chronic obstructive pulmonary disease (COPD) accompanied with PAH [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%